A Practice Based Approach to Complex Organisational Change - Nazila Razi; Elizabeth More (STIE Malangkucecwara, 2017)
This research takes a practice-based approach to examine the formation of integration networks after an acquisition. Drawing on the central principle of agency given to non-human actors in Latour’s (2005) performative theory human and nonhuman actors such as financial reports were traced to investigate how these coalesce in the formation and sustaining of a punctualized post-acquisition integration network.